Criminal Liability of Legal Entities for Environmental Crimes: Problems of Law Enforcement Practice - Danylevska, Yuliia; Sokur, Tatyana; Bodnaruk, Oleksandr; Shevchuk, Andrii; Stratiy, Oleksiy (Fondo Editorial Serbiluz,Universidad del Zulia. Maracaibo-Venezuela, 2021)
The aim of the article was to conduct a comparative legal analysis of the features and problems of criminal prosecution of legal entities for environmental crimes. The research objectives were fulfilled through modern methods of cognition. The leading practical method was the method of observation. The study allowed to form a conceptual understanding of theoretical ideas about environmental crimes of legal entities in Ukraine. Currently, Ukraine is trying to focus in its legislative innovations on the implementation of progressive approaches to the introduction of a comprehensive institution of criminal law measures regarding the liability of these entities. Relevant legal mechanisms and comments identified in the practice of the European Union and substantiated by scholars, can be implemented in the legislation of Ukraine. Amendments to the rules governing the procedure for effective prevention of environmental crimes by legal entities are proposed. It seems reasonable to introduce an active monitoring analysis of anthropogenic activities of companies, and the creation of special units to identify relevant violations. The mechanisms for implementing the set of preventive and monitoring measures outlined in the article, set the background for further scientific research.
Keywords: environmental crime; criminal liability; anthropogenic impact; legal entities; environmental crime